Advances in the Study of Bioactive Compounds and Nutraceutical Properties of Goji Berry (Lycium barbarum L.) - Xin Shi; Xiaojing Wang; Yuhong Zheng; Li Fu (Applied Sciences)
This review examines the nutritional composition, bioactive compounds, and potential health benefits of goji berries (Lycium barbarum L.). Goji berries contain significant amounts of carbohydrates (46–87% dry weight), proteins (5.3–14.3% dry weight), and dietary fiber (3.63–16 g/100 g fresh weight). They are rich in micronutrients, including vitamin C (2.39–48.94 mg/100 g fresh weight) and potassium (434–1460 mg/100 g fresh weight). The berries’ unique polysaccharides, particularly Lycium barbarum polysaccharides (LBPs), exhibit molecular weights ranging from 10 to 2300 kDa. Flavonoids, such as quercetin and rutin (1.0–1.3 mg/g dry weight), and carotenoids, especially zeaxanthin (0.5–1.2 mg/g dry weight), contribute to the berries’ antioxidant properties. In vitro and animal studies have demonstrated various health benefits, including antioxidant, anti-inflammatory, and immunomodulatory effects. However, more human clinical trials are needed to confirm these findings. The review also highlights the impact of geographical origin, cultivation practices, and processing methods on nutrient composition, emphasizing the need for standardization in research and commercial applications. Future research should focus on the bioavailability, metabolism, and potential synergistic effects of goji berry compounds.